Makhdūmūn and Easternmost Dawah in Early Modern Philippines - Isaac Donoso (Islam Nusantara: Journal for the Study of Islamic History and Culture, 2026)
European accounts of early modern insular Southeast Asia document the expansion of Islamic beliefs, institutions, and missionary networks across the Malay Archipelago and into the Pacific frontier. This article examines the role of makhdūmūn and other Islamic preachers in the Islamization of the Philippine Archipelago before and during the early Spanish colonial period. Drawing on European chronicles, Spanish administrative records, indigenous tarsilas, genealogical traditions, epigraphic evidence, and the Boxer Codex, the study reconstructs the activities of Muslim missionaries and the broader transregional networks that connected the Philippines with the Islamic world. The findings demonstrate that Islamization was not an isolated or localized phenomenon but part of a continuous maritime process linking Arabia, India, Persia, China, the Malay world, and the easternmost islands of Southeast Asia. Muslim preachers, traders, and religious scholars introduced Qur’anic teachings, established mosques, legitimized emerging Islamic polities, and integrated local communities into the wider umma. Spanish sources further reveal that colonial authorities perceived these missionary activities as a significant challenge, leading to systematic efforts to suppress Islamic preaching and replace it with Catholic evangelization. This study argues that the early history of the Philippines cannot be fully understood without recognizing the extensive Islamic missionary movement that preceded Spanish rule. Recovering the role of the makhdūmūn highlights the Philippines as the eastern frontier of a dynamic Islamic ecumene and restores a largely overlooked chapter in the religious history of maritime Southeast Asia.